2019
DOI: 10.1039/c9ra07397c
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable iron oxide nanoparticle synthesis within recombinant ferritins from the hyperthermophile Pyrococcus yayanosii CH1

Abstract: Thermostable nanoparticles have numerous applications in catalysis and in the oil/gas industry. However, synthesizing these nanoparticles requires expensive polymers. Here, a novel thermostable ferritin named PcFn, originally from the hyperthermophilic archaeon Pyrococcus yayanosii CH1, was overexpressed in Escherichia coli, purified and characterized, which could successfully direct the synthesis of thermostable magnetoferritins (M-PcFn) with monodispersed iron oxide nanoparticles in one step. Transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…One of the ways to produce magnetite nanoparticles with uniform dimensions is to perform the reaction in constrained environments. Different synthetic and biological reactors could be used for this synthesis, such as apoferritin protein cages [ 50 ], phospholipid membranes (micelles) [ 51 ], mesoporous materials [ 52 ], microemulsions [ 53 ], etc. Here, we would focus on apoferritin protein cages as constrained environments for magnetite nanoparticles synthesis.…”
Section: Synthesis and Characterization Of Magnetite Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the ways to produce magnetite nanoparticles with uniform dimensions is to perform the reaction in constrained environments. Different synthetic and biological reactors could be used for this synthesis, such as apoferritin protein cages [ 50 ], phospholipid membranes (micelles) [ 51 ], mesoporous materials [ 52 ], microemulsions [ 53 ], etc. Here, we would focus on apoferritin protein cages as constrained environments for magnetite nanoparticles synthesis.…”
Section: Synthesis and Characterization Of Magnetite Nanoparticlesmentioning
confidence: 99%
“…Ferritin is an iron storage protein and has a spherical protein cage with an exterior diameter of 12 nm and an interior cavity diameter of 6–8 nm. Yu et al [ 50 ] have a reported novel thermostable ferritin (PcFn), purified and characterized, that could successfully direct the synthesis of thermostable magnetoferritins (M-PcFn) with monodispersed iron oxide nanoparticles in one step. They obtained good crystalline and superparamagnetic magnetite nanoparticles with an average diameter of 4.7 nm ( Figure 4 ).…”
Section: Synthesis and Characterization Of Magnetite Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we synthesized magnetoferritin within a ferritin cage (PfFn) from the hyperthermophilic archaeon Pyrococcus furiosus by adding theoretical loading factors of 10,000 Fe/cage at temperatures of 45 °C, 65 °C, 90 °C, and 95 °C, named MPfFn-45, MPfFn-65, MPfFn-90, and MPfFn-95, respectively. PfFn is considered to be the most thermostable ferritin so far, with a melting temperature (T m ) of >120 °C or 116.8 °C measured under different conditions [ 20 , 21 ]. Compared with mammalian ferritins, such as recombinant human H chain ferritin (T m = 77 °C) [ 22 ], PfFn has a much higher thermostability as well as a different inner structure.…”
Section: Introductionmentioning
confidence: 99%
“…1,[5][6][7] Therefore, researchers have spent great effort to develop fabrication methods to obtain nanoparticles with controllable size, shape, phase and elemental distribution. 4,[8][9][10][11][12][13][14][15] Among all the methods, chemical synthesis and gas-phase deposition are two outstanding ways as they show signicant efficiency, controllability, and exibility on the design and tuning of the nanoparticle structures. Although the chemical synthesis has gained big success in fabricating a large variety of functional nanoparticles with well-designed structures and morphologies, the use of surfactants frequently leads to a critical problem that the synthesized nanoparticles inevitably have organic molecules covered on the surfaces, largely weakening their activities in a lot of sensor applications.…”
Section: Introductionmentioning
confidence: 99%